Cu‐doped Ni3S2 Interlaced Nanosheet Arrays as High‐efficiency Electrocatalyst Boosting the Alkaline Hydrogen Evolution. Issue 7 (10th February 2021) - Ding, Yangyang; Du, Xiaoqiang; Zhang, Xiaoshuang
Abstract: Ni3 S2 has been widely reported as an effective electrochemical catalyst for hydrogen evolution reaction (HER). However, the electrochemical activity of the cathode reduction reaction needs to be further improved due to the drawback of strong S−H bond interaction on the surface of Ni3 S2 . Herein, a series of non‐precious metal Cu element doped Ni3 S2 materials were prepared on the Nickel foam support (Cu−Ni3 S2 /NF) though a two‐step hydrothermal method. Moreover, we optimized the performance of the catalyst by adjusting the molar amount of doped copper ion in the first hydrothermal process. When the molar ratio of copper ion and nickel ion is 1 : 4, the Cu−Ni3 S2 /NF‐1/4 material with independent and clustered rose‐shaped cross‐nanosheet arrays structure have been used as a highly efficient electrochemical hydrogen evolution reaction (HER) catalyst. In HER process, the Cu−Ni3 S2 /NF‐1/4 material drives the current densities of 10 mA cm −2 and 50 mA cm −2 under low overpotentials of 92 mV and 256 mV respectively, while Ni3 S2 /NF needs 210 mV and 397 mV to reach the same current densities. Density functional theory (DFT) calculation shows that the superior electrocatalytic activities are attributed to optimized water adsorption energy and enhanced electrical conductivity. The stability of catalyst was tested in 1 M KOH for 12 hours by chronoamperometry, indicating the current density has no an apparent attenuation. Abstract : Getting a boost : Density functional theory (DFT) calculations and experimental results show that superior activity of Cu−Ni3 S2 is attributed to increased conductivity and increased water adsorption energy due to Cu doping.